Institutional change in the world polity: international human rights and the construction of collective identities - Koenig, Matthias (International sociology, 2008)
This article discusses the transformation of the classical nation-state, as articulated in contemporary struggles for recognition. Elaborating neoinstitutional world polity theory, it analyses global institutional changes that underlie those transformations. It is claimed that the worldwide diffusion of the classical nation-state model itself has had paradoxical consequences, which have in the long run generated a new model of multicultural citizenship, legitimating the decoupling of state membership, individual rights and national identity. The argument is based on empirical evidence from a semantic analysis of international legal discourse on human rights, particularly in the field of religion. Documentary sources suggest that the content of human rights has changed in the second half of the 20th century; the close link between human rights and national self-determination was superseded by the idea that the protection of human rights requires states to recognize a diversity of primordial or traditional identity groups.